2001
DOI: 10.3748/wjg.v7.i5.678
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and pathological characteristic of new type gosling viral enteritis first observed in China

Abstract: AIM To study the purifying method and characteristics of new gosling viral enteritis virus (NGVEV), the etiological agent of new gosling viral enteritis (NGVE) which was first recognized in China, as well as the pathomorphological development in goslings infected artificially with NGVEV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The new type gosling viral enteritis (NGVE) is a new infectious disease and firstly recognized by Cheng et al, and it was observed in goslings less than 30 d of age in various areas of Sichuan Province [17,18] . The mortality from acute NGVE is high, and it is clinically characterized by respiratory, digestive, and neurological symptoms and www.wjgnet.com sudden death [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new type gosling viral enteritis (NGVE) is a new infectious disease and firstly recognized by Cheng et al, and it was observed in goslings less than 30 d of age in various areas of Sichuan Province [17,18] . The mortality from acute NGVE is high, and it is clinically characterized by respiratory, digestive, and neurological symptoms and www.wjgnet.com sudden death [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The new type gosling viral enteritis (NGVE) is a new infectious disease and firstly recognized by Cheng et al, and it was observed in goslings less than 30 d of age in various areas of Sichuan Province [17,18] . The mortality from acute NGVE is high, and it is clinically characterized by respiratory, digestive, and neurological symptoms and www.wjgnet.com sudden death [17][18][19] . Catarrhal hemorrhagic fibrinonecrotic enteritis of the small intestine and coagulative embolus in the lower middle part of the intestine are the typical pathological changes of the NGVE in infected goslings [18] .…”
Section: Introductionmentioning
confidence: 99%
“…The minimal lethal dose of the virus suspension (LD 50 ) was 10 6.5±1.3 /0.5 mL. This strain has been previously described [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Experimental Goslings and Virus Strainmentioning
confidence: 99%
“…An increasing number of viruses or viral gene products have been reported to induce apoptosis [17,22,26,30]. New type gosling viral enteritis (NGVE) is an infectious disease that affects goslings less than 30 days of age, and is caused by an adenovirus called the NGVE virus (NGVEV) [4,5,12,13,15,27,40]. In gosling-producing areas, NGVE has resulted in significant economic losses due to the high mortality of the offspring of breeder geese [12,27].…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus infection of the kidney is seen in a variety of birds [29,30]. Grossly there may be some nonspecific renal enlargement.…”
Section: Viralmentioning
confidence: 99%